2018
DOI: 10.3390/min8020042
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry, Mineralogy and Microbiology of Molybdenum in Mining-Affected Environments

Abstract: Abstract:Molybdenum is an essential element for life, with growing production due to a constantly expanding variety of industrial applications. The potentially harmful effects of Mo on the environment, and on human and ecosystem health, require knowledge of Mo behavior in mining-affected environments. Mo is usually present in trace amounts in ore deposits, but mining exploitation can lead to wastes with very high Mo concentrations (up to 4000 mg/kg Mo for tailings), as well as soil, sediments and water contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 87 publications
0
14
0
2
Order By: Relevance
“…6466 To prevent such detrimental environmental effects, the processes controlling oxyanion concentrations in mine drainage need to be understood. Although selected studies have investigated the occurrence, (bio)geochemical dynamics, and toxicity of As, Mo, Sb, and Se in mine wastes (e.g., for As, 2225 Mo, 14,26,27 Sb, 28,29 and Se 3032 ), the majority of these laboratory and field studies has focused on their behavior under acidic conditions, with relatively little attention given to neutral- or alkaline-pH waters (e.g., for As 15,33 ). Therefore, the potential sources and environmental fates of these elements in NRD systems remain poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…6466 To prevent such detrimental environmental effects, the processes controlling oxyanion concentrations in mine drainage need to be understood. Although selected studies have investigated the occurrence, (bio)geochemical dynamics, and toxicity of As, Mo, Sb, and Se in mine wastes (e.g., for As, 2225 Mo, 14,26,27 Sb, 28,29 and Se 3032 ), the majority of these laboratory and field studies has focused on their behavior under acidic conditions, with relatively little attention given to neutral- or alkaline-pH waters (e.g., for As 15,33 ). Therefore, the potential sources and environmental fates of these elements in NRD systems remain poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…This latter mineral is typical of granitoid rocks outcropping in different Arctic regions (e.g, N-Norway and E-Greenland), and only small outcrops of these rocks were found in the northernmost Svalbard (Johansson et al, 2002). In coal mining regions, however, Mo is usually present in trace amounts in ore deposits, but it can be enriched due to exploitation (Frascoli and Hudson-Edwards, 2018). Also, Mo associated with over bank deposits from Triassic rocks has low content in sediments.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of surface water is important for life on Earth . Understanding the mobility of trace elements in natural waters and the ability to predict changes in that mobility are important research topics in environmental geochemistry. , Molybdenum (Mo) is one of the transition elements that are essential for living organisms, but it is harmful in large doses. Since the turn of the century, considerable attention has been paid to the environmental behavior of Mo in natural waters. , In 2011, the World Health Organization (WHO) established a guideline concentration of 70 μg/L for Mo in drinking water on the basis of toxicological evidence and the essential daily human requirement for Mo . The U.S. Environmental Protection Agency determined a lifetime advisory level of 40 μg/L Mo in surface water.…”
Section: Introductionmentioning
confidence: 99%
“…The samples with Mo concentrations that exceed 70 μg/L were only 0.1% of samples from U.K. rivers and were not reported in samples from rivers in India 13 and France. 14 Reviews of Mo concentrations in rivers affected by mining activities 3,4 have identified increased Mo concentrations in pore water in tailings dumps and acidic mine drainage water, 15,16 although most mining-affected river waters do not exceed the WHO guideline level, except for an area around the Climax molybdenum mine (United States) during the 1970s. 15 The Erdenet mine in Mongolia is one of the world's largest copper−molybdenum mines.…”
Section: ■ Introductionmentioning
confidence: 99%